Nutrition and physical capacity development (Colombia Medica, 1992)
The functional consequences of nutritional deprivation are reviewed regarding maximal oxygen consumption, physical work capacity, heart rate response to exercise, work productivity in adults, and its effects on children's growth and development of physical work capacity. The results of chronic marginal malnutrition and the effects of dietary supplementation and recovery from previously existing undernutrition are considered.